HUBUNGAN ANTARA PENGETAHUAN, SIKAP, DAN PRAKTIK IBU DALAM PEMBERIAN MAKANAN PENDAMPING ASI (MPASI) PADA ANAK USIA 6-24 BULAN DENGAN KEJADIAN STUNTING DI WILAYAH KERJA PUSKESMAS SINGGAHAN, KABUPATEN TUBAN - Siti Mahfirotun Nimah; Dyah Mahendrasari Sukendra (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Stunting is a chronic nutritional problem caused by many factors such as socioeconomic conditions, maternal nutrition during pregnancy, child morbidity, and child malnutrition. Complementary Foods can meet the nutritional needs of the baby's body which can no longer be supported by breast milk, as well as build the body's resistance and the development of the child's immune system against food and drink. The purpose of this study was to determine the relationship between knowledge, attitudes, and practices of mothers in giving complementary foods to children aged 6-24 months and the incidence of stunting in the working area of the Puskesmas Singgahan. This type of research is analytic observational with a cross-sectional design. The sampling technique used was proportionate simple random sampling. Samples were taken from as many as 38 respondents. Data were collected by conducting direct interviews using a questionnaire. Data analysis was performed in univariate, bivariate, and multivariate. The results showed that there was a relationship between the mother's knowledge about complementary foods p=0.030), the mother's attitude in giving complementary foods (p=0.019), the mother's practice in giving complementary foods (p=0.009) with the incidence of stunting. Based on the multivariate analysis, the variable of the mother's practice in giving complementary foods is the variable that has the most strong contribution to predicting stunting. The suggestion from this study is that mothers or child caregivers have to increase their knowledge and practice in giving complementary foods by frequently seeking information that is supported by an attractive stunting prevention program from the government.